Going Concern Audit Opinion Reviewed from The Company's Financial Condition, Audit Tenure, and Audit Opinion in the Previous Year - Olimsar, Fredy (Future Science, 2022)
The purpose of this research is to examine the impact of the company's financial condition, audit tenure, and previous year's audit opinion on acceptance of the Going concern audit. This study's sample consists of transportation sector companies listed on the IDX from 2017 to 2020. Purposive sampling was used in this study, and a total of 112 data were obtained from as many as 28 companies. Logistic regression analysis was used to test hypotheses using SPSS 25 software. The findings revealed that the Company's Financial Condition, Tenure Audit, and previous year's audit Opinion all had an impact on Going Concern audit acceptance. The acceptance of the Going concern audit opinion was influenced in part by the company's financial condition and the previous year's audit opinion. While the Tenure Audit has a minor impact on the acceptance of the Going Concern audit opinion.